Ways to Expand the Position of the Production Enterprise in the Market of Yarn and Knitted Products - Ikramova Taxmina Latifovna (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
In this article, the current development level of the textile products market, the trend of increasing demand for natural and organic materials, the trend of attention to sustainable and ethical practices, the trend of high demand for traditional designs, and the emerging trend of online commerce.